2008
DOI: 10.1115/1.2948399
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Laplace-Wavelet Combined With ANN for Rolling Bearing Fault Diagnosis

Abstract: A new technique for an automated detection and diagnosis of rolling bearing faults is presented. The time-domain vibration signals of rolling bearings with different fault conditions are preprocessed using Laplace-wavelet transform for features’ extraction. The extracted features for wavelet transform coefficients in time and frequency domains are applied as input vectors to artificial neural networks (ANNs) for rolling bearing fault classification. The Laplace-Wavelet shape and the ANN classifier parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Yang et al [ 16 ] proposed that vibration signals can be decomposed to stationary intrinsic mode functions (IMFs), and the input of ANN is the energy features extracted from IMF so as to identify the rolling bearing failure. Al-Raheem et al [ 17 ] proposed a new technique that used genetic algorithm to optimize the application of Laplace wavelet shape and classifier parameters of ANN for bearing faults. In addition, Shuang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [ 16 ] proposed that vibration signals can be decomposed to stationary intrinsic mode functions (IMFs), and the input of ANN is the energy features extracted from IMF so as to identify the rolling bearing failure. Al-Raheem et al [ 17 ] proposed a new technique that used genetic algorithm to optimize the application of Laplace wavelet shape and classifier parameters of ANN for bearing faults. In addition, Shuang et al.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of combined method May be difficult to interpret Merging two or methods may result in a time-consuming and/or power-consuming issue FDD [127][128][129][130][131][132][133][134][135][136][137][138][139], [141][142][143][144][145][146][147][148][149][150][151][152] Fault prognosis [126], [140] Although the deep learning is not a new concept, it has only recently started to gain more attention and to be successfully applied in different fields, such as computer vision, language and audio processing, and (automatic) recognition [153], [154]. It is only in the last few years that deep learning started to be applied to the PHM field [155][156][157].…”
Section: Deep Learning For Reb Phmmentioning
confidence: 99%
“…In frequency-based analysis, the bearing fault is detected by checking if there exists a pronounced spectral component in the resulting spectra that corresponds to one of the bearing characteristic defect frequencies. If the frequency-based fault detection technique cannot enhance the bearing health condition-related spectral components (i.e., making them pronounced or dominant in the spectral maps), other supplementary methods, based on either time-domain or time-frequency-domain analysis, should be properly employed to improve the diagnostic accuracy [2,16]. In our investigation, it is found that when the bearing is in its normal condition, the shaft speed dominates the resulting spectra due to unavoidable imperfections (e.g., system unbalance).…”
Section: Performance Validationmentioning
confidence: 99%
“…In bearing fault diagnosis, the WT is a favorite technique, because it does not contain such cross terms as those in the Wigner-Ville transform, while it can provide a more flexible multi-resolution solution than the short-time FT. According to signal decomposition paradigms, the WT can be classified as the continuous WT, discrete WT, wavelet packet analysis, and those WT with post-processing schemes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%